CONCEPTUAL UNDERSTANDING IN SECONDARY MATHEMATICS EDUCATION: A SYSTEMATIC REVIEW OF RESEARCH APPROACHES AND PEDAGOGICAL INTERVENTIONS - Miftahul Atiqoh; M Farhan Ainun Ihsani; Ulfah Zulaikha; Masduki Masduki (Prima: Jurnal Pendidikan Matematika, 2026)
Conceptual understanding constitutes a critical foundation in secondary mathematics, yet students often struggle to connect concepts with appropriate representations. Existing literature reviews remain fragmented, necessitating a comprehensive synthesis of research approaches and pedagogical interventions across studies. This study aims to map research approaches, identify effective pedagogical interventions, analyze assessment characteristics, and determine dominant mathematical topics. A Systematic Literature Review (SLR) using the PRISMA protocol analyzed 17 articles from Scopus and ERIC databases published between 2020 and 2025. Findings reveal that quantitative approaches dominate the field, while qualitative methods provide depth in cognitive mapping. Pedagogical interventions are categorized into structured non-digital strategies, technology integration, and socio-cultural approaches. Assessment methods primarily rely on tests, complemented by process-based evaluations and mixed evidence to capture reasoning structures. Research concentration focuses heavily on algebra and functions, followed by geometry and calculus.